Do Vote-Buyers Target the Poor? Evidence from Elections in the Philippines - Canare, Tristan A (Archīum Ateneo, 2016)
As a contribution to the nascent literature, this study examines patterns of vote buying among poor voters in 17 cities in Metro Manila, using a dataset closely following the 2016 national and local elections. Specifically, it will examine the possible factors linked to vote buying, hopefully uncovering evidence on whether and how this is targeted at poor voters. This study also looks at the correlates of other aspects of vote buying, including of accepting the offer and of voting for the candidate who made the offer. The main focus is on the poor because extensive anecdotal evidence suggests that this could be the group most prone to sell their votes, in large part because of their needs. This paper finds evidence that vote buying among poor voters in Metro Manila appears to be a finely targeted activity, wherein various things of value can be used to buy votes, while money is used only in tight Mayoral races.